005 Clinical Practice Guidelines and Systematic Reviews: Point of Intersection?. (15th August 2013) - Wilson, L; Robinson, K
Abstract : Background: Guideline committees (GCs) rely on the evidence synthesised in systematic reviews (SRs) to develop evidence-based guidelines. Institute of Medicine standards for clinical practice guidelines include an interaction between the GC and the team conducting the SR. Context: In 2005, the Cystic Fibrosis Foundation moved from consensus-based to evidence-based guideline development. SRs are now commissioned to inform specific guidelines. A methodologist, serving as a member of each multidisciplinary GC and as the lead investigator for the SR teams, provides the link for the scope, approach, and output of both processes. Description of Best Practice: The methodologist, as part of the GC, facilitates the definition of the scope and refines the questions for the SRs. The methodologist oversees the conduct of the SR, ensuring that the review team addresses relevant questions, appropriately conducts searches, and establishes inclusion criteria and provides informative details to the GC. The methodologist provides training, where needed, and ensures consistency across guidelines in the drafting and grading of the recommendations. The methodologist also helps to address peer review comments and draft the guideline documents. Lessons for Guideline Developers, Adaptors, Implementers, and/or Users: Having a methodologist serve on both the GC and the SR team ensures that there is appropriate and timely intersection of the guideline and SR processes. The methodologist can ensure that the SR team meets the needs of the GC and illuminate for the GC the methods and outcomes of the SR.